2017
DOI: 10.1634/theoncologist.2017-0227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Integrated Palliative Care on Caregivers of Patients with Lung and Gastrointestinal Cancer: A Randomized Clinical Trial

Abstract: This article reports a single‐center randomized clinical trial that evaluated the effect of early integrated specialty palliative care on patient‐ and caregiver‐reported outcomes in patients with newly‐diagnosed, incurable cancers. It was hypothesized that caregivers of patients assigned to early integrated palliative care would report lower psychological distress and better quality of life compared with caregivers of patients assigned to usual oncology care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
174
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(184 citation statements)
references
References 34 publications
3
174
1
3
Order By: Relevance
“…In this section, we focus on more recent publications, because older studies have been summarized in previous reviews . Table highlights the key elements of study design and outcomes . A majority of these clinical trials concluded that concurrent palliative care improves quality of life, symptoms, and patient‐clinician communication compared with oncologic care alone .…”
Section: Evidence To Support Early Palliative Carementioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we focus on more recent publications, because older studies have been summarized in previous reviews . Table highlights the key elements of study design and outcomes . A majority of these clinical trials concluded that concurrent palliative care improves quality of life, symptoms, and patient‐clinician communication compared with oncologic care alone .…”
Section: Evidence To Support Early Palliative Carementioning
confidence: 99%
“…A majority of these clinical trials concluded that concurrent palliative care improves quality of life, symptoms, and patient‐clinician communication compared with oncologic care alone . Some studies also demonstrated that palliative care enhances mood, patient satisfaction, quality of end‐of‐life care, survival, and caregiver outcomes (Table ) . Of note, none of the studies favored oncologic care alone for the primary outcome.…”
Section: Evidence To Support Early Palliative Carementioning
confidence: 99%
See 1 more Smart Citation
“…The routine integration of PC referral into the outpatient transplantation assessment process has been shown to significantly improve the symptoms of patients with ESLD, impacting positively on depression, pruritus, appetite, anxiety, and fatigue . In surgical and oncology settings, early incorporation of PC has been demonstrated to increase family goals of care consensus and advance directive planning, but this has not yet been shown for patients with ESLD . This is likely related to a difference in the perceived prognosis of the underlying condition.…”
Section: Quality Of Life and Palliative Managementmentioning
confidence: 99%
“…The first randomized controlled trials (RCTs) published in high‐impact journals provided evidence that concurrent palliative care could have positive effects on quality of life, depression, symptom burden, satisfaction with care, and survival among individuals who were living with metastatic solid tumors. The evidence base continued to expand beyond these seminal studies and demonstrated positive effects on illness communication, adaptive coping, prognostic awareness, treatment decision making, end‐of‐life care, caregiver outcomes, and cost‐effectiveness . As the science matured, palliative care researchers were able to identify mediators and moderators of the beneficial effects of palliative care …”
Section: Strategy 1: Stimulating the Science In Specific Gap Areasmentioning
confidence: 99%